2009
DOI: 10.4193/rhin08.180
|View full text |Cite
|
Sign up to set email alerts
|

Ventilation and aerosolized drug delivery to the paranasal sinuses using pulsating airflow aeuro" a preliminary study

Abstract: The study demonstrates the high efficiency of a pulsating airflow in paranasal sinus ventilation and aerosolized drug delivery. This proves that topical drug delivery to the paranasal sinuses in relevant quantities is possible and indicates further clinical studies are necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
86
0
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(96 citation statements)
references
References 28 publications
5
86
0
5
Order By: Relevance
“…Due to the small dimensions of the ostium, drainage in the nasal cavity is impaired in CF, and chronic sinusitis is therefore found in nearly all patients. It has been shown that microaerophilic conditions are encountered (Aanaes et al, 2011), that fewer PMNs are present surrounding the bacteria and that lower antibiotic concentrations are achieved in the sinus compared to the lung, since the nebulized antibiotics do not reach the paranasal sinuses (Moeller et al, 2009). …”
Section: Discussionmentioning
confidence: 99%
“…Due to the small dimensions of the ostium, drainage in the nasal cavity is impaired in CF, and chronic sinusitis is therefore found in nearly all patients. It has been shown that microaerophilic conditions are encountered (Aanaes et al, 2011), that fewer PMNs are present surrounding the bacteria and that lower antibiotic concentrations are achieved in the sinus compared to the lung, since the nebulized antibiotics do not reach the paranasal sinuses (Moeller et al, 2009). …”
Section: Discussionmentioning
confidence: 99%
“…Based on previous studies (Maniscalco, 2006;Möller et al, 2008Möller et al, , 2009Durand et al, 2001;Valentine et al, 2008), specific nasal jet nebulizers using sound effects are currently the best option for targeting antibiotic aerosols to the site of infection in case of chronic rhinosinusitis. This study demonstrates that aerosols produced by these specific nasal sonic jet nebulizers using sound effect are deposited in the anatomical targets to treat sinusitis.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, based on the (Möller et al, 2008) method using 81m Kr gas, we used a specific nasal sonic jet nebulizer with sound effect that enables gas to penetrate the maxillary sinuses and hence allows anatomical regions to be determined. With the nasal sonic jet nebulizer with sound effect, aerosol deposited in volunteers' lungs was similar to results obtained from Pari jet nebulizer without sound effect (Djupesland et al, 2004) (27 ± 10% vs 22 ± 8.1%), demonstrating that the sound effect has no significant effect on lung deposition.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations